Human immunodeficiency virus type-1 reverse transcriptase. Contribution of Met-184 to binding of nucleoside 5'-triphosphate - Wilson, J E; Aulabaugh, A; Caligan, B; McPherson, S; Wakefield, J K; Jablonski, S; Morrow, C D; Reardon, J E; Furman, P A (The Journal of biological chemistry, 1996)
Mutations were made in recombinant human immunodeficiency virus type-1 reverse transcriptase (RT) by substituting methionine 184 with alanine (M184A) or valine (M184V), and steady-state and pre-steady-state kinetic constants were determined. The Km values of M184A RT for dNTPs were larger than those of wt RT for RNA-directed synthesis; the kcat values of M184A RT for processive or distributive synthesis were similar. In contrast to M184A RT, the Km and kcat values of M184V RT for dNTP substrates were similar to those of wt RT. The Ki values of M184V RT for 1-beta-L-nucleoside analogs were increased 30-500-fold relative to wt RT for both RNA- and DNA-directed synthesis. The Kd and kp values of wt RT and M184V RT for dCTP and cis-5-fluoro-1-[2-(hydroxymethyl)-1, 3-oxathiolan-5-yl]cytosine 5'-triphosphate (1-beta-L-FTCTP) were estimated from pre-steady-state kinetics for single nucleotide incorporation. The Kd value of M184V RT for 1-beta-L-FTCTP was 19-fold greater than that of wt RT; the kpvalues of the two enzymes were similar. These results support the hypothesis that methionine 184 in the highly conserved YMDD region of wt RT participates in the binding of the nucleoside (analog) 5'-triphosphate.